Comparative studies on Fenton-like reactions catalyzed by Fe3O4 loaded inside and outside halloysite nanotubes for the removal of organic pollutants - Li, Yang; Zhou, Jia-Qi; Xu, Huan-Yan; Dong, Li-Min; Cao, Mao-Chang; Shan, Lian-Wei; Jin, Li-Guo; He, Xiu-Lan; Qi, Shu-Yan (Frontiers of materials science, 2024)
In this work, Fe 3 O 4 nanoparticles (NPs) loaded inside and outside halloysite nanotubes (HNTs) were prepared and developed as the heterogeneous Fenton-like catalysts for the removal of representative organic pollutants. Characterization results indicated that the samples with Fe 3 O 4 NPs loaded outside the HNTs lumen (Fe 3 O 4 /HNTs) and inside the HNTs lumen (Fe 3 O 4 @HNTs) were successfully prepared. Both samples had typical magnetic hysteresis loops, while Fe 3 O 4 @HNTs exhibited higher magnetization intensity. The comparative experiments showed that Fe 3 O 4 @HNTs had better Fenton-like catalytic ability than that of Fe 3 O 4 /HNTs in the degradation of various organic pollutants. Taking Rhodamine B (RhB) as an example, the adsorption thermodynamics and kinetics of RhB onto Fe 3 O 4 /HNTs and Fe 3 O 4 @HNTs were also investigated. The comparative results demonstrated that the adsorption ability of Fe 3 O 4 /HNTs was better than that of Fe 3 O 4 @HNTs. Moreover, the dissolved concentration of Fe 2+ and production amount of hydroxyl radical (·OH) in the Fe 3 O 4 @HNTs-H 2 O 2 system were significantly higher than those in the Fe 3 O 4 /HNTs-H 2 O 2 system. Based on aforementioned comparison, the nano-confinement effect in the Fe 3 O 4 @HNTs-H 2 O 2 system was verified. This work provides meaningful guidance for the cheap and convenient design of nanoreactors for Fenton-like applications.